The detection and policing of gun crime: Challenges to the effective policing of gun crime in Europe. (March 2018) - Hellenbach, Mike; Elliott, Sue; Gerard, F. Jeane; Crookes, Becky; Stamos, Thanos; Poole, Helen; Bowen, Erica
Despite a shared understanding across the European Union (EU) that access to firearms by the general public should be restricted, detailed legislation regarding the ownership, use and trade of firearms varies between EU member states. It is unclear, however, how such variations impact on the policing of gun-enabled crime. By using qualitative data generated from interviews with police, policy and decision makers from 13 European countries, we aim to determine how stakeholders perceive that national variations in firearms legislation affect the policing of gun-enabled crime within and across EU countries. Four main themes were identified from the qualitative data: disparities in legislation, disparities in the priority given and the resources allocated to investigations into gun-enabled crime, as well as interventions. Owing to the aforementioned disparities, cross-national investigations into incidents of gun crime are at risk of remaining impaired in their effectiveness. Therefore, more legislative coherency as well as sustainable long-term interventions will be needed to successfully reduce ownership and use of firearms in the criminal world. In this context, a departure from an exclusive use of an economic model of gun crime is recommended to allow for a better understanding of the dynamics of the black gun market.